Digital Media Skills among Different Stakeholders and their Attitude towards MOOCs in Higher Education Institutions - Adit Gupta; Nishta Rana; Mool Raj (Universitas Negeri Makassar, 2024)
This study aims to examine the digital media skills among different stakeholders in higher education institutions in relation to their gender, age and qualifications as well as their attitude towards MOOCs. A descriptive survey method was used for the study. The sample consists of 1478 stakeholders (1278 students, 90 teachers, 107 parents and 3 administrators) from different higher education institutions of Jammu region selected using simple random sampling. The data has been collected by employing two self-constructed tools namely the Digital Media Skill Scale (DMSS) and the Attitude Towards MOOCs Scale (ATMS). Findings show that all the stakeholders have good digital media skills. Male stakeholders were found to have better digital media skills than female stakeholders. There was no significant difference in the skills regarding digital media as far as the qualification of stakeholders is concerned. Younger stakeholders (less than 30 years of age) were found to have better skills than older ones. Teachers were found to be better than students, students were found to be better than administrators and parents. Regarding the attitude towards MOOCs, all stakeholders were found to have a positive attitude. No significant gender, as well as qualification differences, emerged with respect to their attitude towards MOOCs. Younger stakeholders (less than 30 years of age) were found to have more positive attitudes towards MOOCs than older ones. Teachers were found to have better attitudes towards MOOCs than students and students were found to have better attitudes than administrators and parents.